Pengaruh Aplikasi Augmented Reality Berbasis Budaya Melayu Terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Ayu Safitri; Nur Rahmi Rizqi; Ulfa Annisa Lubis (CV. Rayyan Dwi Bharata, 2025)
This study aims to explore the influence of Malay culture-based Augmented Reality applications on students' understanding of mathematical concepts. This study uses two Augmented Reality methods: Marker-Based Tracking and Markerless Augmented Reality, to present mathematical materials with a culture-based approach. The Marker-Based Tracking method uses image markers to display virtual objects, while Markerless Augmented Reality utilizes markerless tracking technologies, such as Face Tracking and GPS. The research method involved two classes at MTS EX PGA Univa Medan: class VII-1 as an experimental group using the Malay culture-based Augmented Reality application and class VII-2 as a control group using the Scientific Approach. Data was collected through pretest and posttest consisting of essay questions to measure students' understanding of mathematical concepts. The validity and reliability of the instrument were tested, and data analysis was carried out using SPSS Statistics 26 for normality, homogeneity, and hypothesis tests. The results of the study show that the application of Augmented Reality based on Malay culture has a significant influence on students' understanding of mathematical concepts. The average posttest score of students in the experimental class reached 74.03, higher than 56.00 in the control class. The Independent Sample T-Test confirmed the significance of the results with a value of p = 0.001 (< 0.05), which showed that the use of Augmented Reality applications based on Malay culture was effective in improving the understanding of mathematical concepts.